EXERCISE STRESS ECHOCARDIOGRAPHY WITH TISSUE DOPPLER IMAGING (TDI) DETECTS EARLY SYSTOLIC DYSFUNCTION IN BETA-THALASSEMIA MAJOR PATIENTS WITHOUT CARDIAC IRON OVERLOAD - Umberto Barbero (Mediterranean Journal of Hematology and Infectious Diseases)
Iron Overload Cardiomyopathy (IOC) is still the main cause of death in thalassemia major (TM) patients. Unfortunately, Conventional Echocardiography fails to predict early cardiac dysfunction. As Tissue Doppler Imaging (TDI) may demonstrate regional myocardial dysfunction, we wondered if exercise may reveal abnormalities at TDI which are not evident at rest. To try to evaluate left and right myocardial performances at rest and after maximal exercise by both conventional and TDI parameters, 46 beta-TM adult patients and 39 control subjects were enrolled. All patients had a liver iron quantification by Superconducting Quantum Interference Device (SQUID) and also a cardiac iron assessment by MRI (T2*): 38 TM patients had no evidence of cardiac iron overload. Whereas TM patients did not shown diastolic dysfunction and all of them presented a good global response to exercise, TDI detected a reduced increase of the S’ waves of left ventricle basal segment during exercise. This finding seems to have some weak but interesting relations with iron overload markers. In conclusion, in our study, exercise stress TDI-echocardiography was able to demonstrate subtle systolic abnormalities that were missed by Conventional Echocardiography. Further studies are required to determine the meaning and the clinical impact of these results.